The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/548081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Segmentation-Enhanced CycleGAN

Abstract: Algorithmic reconstruction of neurons from volume electron microscopy data traditionally requires training machine learning models on dataset-specific ground truth annotations that are expensive and tedious to acquire. We enhanced the training procedure of an unsupervised image-to-image translation method with additional components derived from an automated neuron segmentation approach. We show that this method, Segmentation-Enhanced CycleGAN (SECGAN), enables near perfect reconstruction accuracy on a benchmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…paintings), without being given any explicit pairings between elements of both sets. Here we extended this method to 3D volumes, and used model architectures and training hyperparameters as previously described (Januszewski and Jain, 2019), but without utilizing the flood-filling module.…”
Section: Image Adjustment With Cyclegansmentioning
confidence: 99%
“…paintings), without being given any explicit pairings between elements of both sets. Here we extended this method to 3D volumes, and used model architectures and training hyperparameters as previously described (Januszewski and Jain, 2019), but without utilizing the flood-filling module.…”
Section: Image Adjustment With Cyclegansmentioning
confidence: 99%
“…In a similar vein, Linsley et al . have shown that the network architectures that exhibit “superhuman” accuracy for the segmentation of neural tissue from serial electron microscopy images when trained and tested on different subsets of the same volume do exhibit a large drop in accuracy when trained and tested on different volumes 81 (for practical applications, the issue can be alleviated using machine learning methods for “realigning” datasets 82 ). By comparison, they found that RNNs endowed with horizontal and top‐down connections can generalize much better and use fewer training examples 66,77 …”
Section: The Role Of Recurrence In Visual Recognitionmentioning
confidence: 99%
“…Similarly, cycle-consistent adversarial networks (CycleGAN) [40] or style transfer GANs [41] may be used to relate the two data domains in cases where pairs are lacking, e.g. for low resolution reconstructions without a matching ground truth or for generalizing the data set to new experimental conditions with few existing examples [42]. Thirdly, the approach described here may be adapted to use optimisation algorithms other than expectation maximisation.…”
Section: Conclusion and Discussionmentioning
confidence: 99%